Advance directives in the perioperative setting: Managing ethical and legal issues when patient rights and perceived obligations of the healthcare provider conflict. Issue 4 (22nd April 2013) - Williams, Stephen P.; Howe, Christopher L.
Abstract Perhaps individual wishes are not always acknowledged or accepted when it comes to end‐of‐life care. This possibility, in conjunction with the experiences of healthcare risk managers, should cause concern in the healthcare risk management community. One particularly concerning issue where a persistent failure to honor a patient's wishes exists is with Do Not Resuscitate (DNR) orders in the perioperative arena. Despite a strong focus on informed consent and advance directives, evidence suggests a number of healthcare organizations either have no policy in place regarding DNR orders during the perioperative period, or, for those organizations that do have a policy, many call for automatic suspension of the DNR order without consultation with the patient. This latter practice poses many ethical, medico‐legal, and regulatory concerns, and healthcare organizations with such a policy in place should strongly consider revisiting this practice.